Selection of MEMS Accelerometers for Tilt Measurements - Grepl, Robert (Hindawi, 2017)
In order to build a tilt sensor having a desired sensitivity and measuring range, one should select an appropriate type, orientation, and initial position of an accelerometer. Practical guidelines for an optimal selection of a particular micromachined accelerometer for a specific case of tilt measurement are provided.

In order to build a tilt sensor having a desired sensitivity and measuring range, one should select an appropriate type, orientation, and initial position of an accelerometer. Practical guidelines for an optimal selection of a particular micromachined accelerometer for a specific case of tilt measurement are provided.
Selection of MEMS Accelerometers for Tilt Measurements
Keywords: sensor; accelerometer; sensor; accelerometer